Evaluation of predictors of mortality in patients of ruptured liver abscess: a prospective study - Faridi, Syed A.; Harris, Syed H.; Alvi, Yasir (International Surgery Journal, 2021)
Background: Ruptured liver abscess is a rare condition which is associated with high mortality. Ruptured liver abscess should be assessed carefully especially in patients with poor prognostic factors, which highlight the need for early diagnosis to further improve our results of management. The aim of the present study was to evaluate the predictors of mortality in patients of ruptured liver abscess. Methods: This was a prospective study, performed at Jawaharlal Nehru medical college, AMU, Aligarh between October 2015 to October 2017. For each case-patient, we reviewed demographic data, underlying medical conditions, clinical features, laboratory data, imaging and microbial findings and treatment. The prognostic factors independently related to mortality were then identified using univariate and multivariate analysis considering significance at p<0.05. Results: The overall in-hospital mortality was 27% (11 out of 40). On multivariate regression analysis, the factors that independently predicted mortality were shock at presentation, time of presentation (>48 hours), left lobe abscess and APACHE II score on admission more than 15. Conclusions: The independent predictors of mortality in ruptured liver abscess are shock at presentation, delayed presentation, higher APACHE II score on admission and left lobe abscess.